2015
DOI: 10.3109/10799893.2015.1030412
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathway of MAPK/ERK in cell proliferation, differentiation, migration, senescence and apoptosis

Abstract: The generic mitogen-activated protein kinases (MAPK) signaling pathway is shared by four distinct cascades, including the extracellular signal-related kinases (ERK1/2), Jun amino-terminal kinases (JNK1/2/3), p38-MAPK and ERK5. Mitogen-activated protein kinases/extracellular signal-regulated kinase (MAPK/ERK) pathway is reported to be associated with the cell proliferation, differentiation, migration, senescence and apoptosis. The literatures were searched extensively and this review was performed to review the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
966
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,423 publications
(991 citation statements)
references
References 71 publications
17
966
1
7
Order By: Relevance
“…Components within the MAPK, ERK and JNK signaling pathways, including insulin, glucocorticoid, hyperbaric oxygen and fibroblast growth factor-6, have been identified as major promoters of osteoblast proliferation in a number of studies (41)(42)(43). Song et al (44) demonstrated that icariin, a flavonoid glucoside isolated from P. corylifolia, promoted MC3T3-E1 osteoblast proliferation by inducing the activation of ERK and JNK, but exerted no effect on the activity of p38 kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Components within the MAPK, ERK and JNK signaling pathways, including insulin, glucocorticoid, hyperbaric oxygen and fibroblast growth factor-6, have been identified as major promoters of osteoblast proliferation in a number of studies (41)(42)(43). Song et al (44) demonstrated that icariin, a flavonoid glucoside isolated from P. corylifolia, promoted MC3T3-E1 osteoblast proliferation by inducing the activation of ERK and JNK, but exerted no effect on the activity of p38 kinase.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK signaling pathway is reported to be associated with the cell proliferation, differentiation, migration, senescence, and apoptosis, including ERK1/2 and JNK. 28 For example, it has been reported that curcumin suppresses proliferation and migration and induces apoptosis on human placental choriocarcinoma cells via ERK1/2 and stress-activated protein kinase (SAPK)/JNK MAPK signaling pathways. 29 Vitexin suppresses autophagy to induce apoptosis in hepatocellular carcinoma via activation of the JNK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the MAPK signaling pathway is known to cause the transformation of normal cells to tumor phenotype (6). Thus, inhibition of this pathway may enable restoration of the tumor cells to the untransformed phenotype in vitro, thereby inhibiting the growth of the tumor in the body (50,51).…”
Section: Regulation Of the Mapk Signaling Pathway For Targeted Oral Cmentioning
confidence: 99%
“…Multiple signaling pathways may function in oncogenesis and in the growth of oral malignancies (4,5). Among these is the mitogen activated protein kinase (MAPK) signaling pathway, which regulates the expression of a large number of proteins involved in the control of cell proliferation, differentiation and apoptosis (6,7), and remains a focus of investigation for therapeutic targeting, along with the development of appropriate inhibitors (8). These inhibitors have been demonstrated to be effective for the treatment of oral cancer and other malignancies, including human colon cancer, breast cancer and lung cancer (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%